HUBUNGAN KECEMASAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Maya Adityana Pranasti; Siti Napfiah (Program Studi Pendidikan Matematika, 2019)
The innovative and fun mathemathics learning are preferred by students. Innovative and fun learning will dissepear views of mathematics that difficult and boring. Thus, it can decreases students anxiety and fresult of learning will increase. The purpose of this study was to dtermine the relationship between mathematics learning anxiety on student result in mathematics subjects at Junior High School Aisyiyah Muhammadiyah 3 Malang. The research used correlation method with a quantitative approach for this study. The results showed that there was a correlation between the anxiety of learning mathematics on student result in mathematics subjects in class VIII-A at Junior High School Aisyiyah Muhammadiyah 3 Malang. It can be evidenced by the correlation coefficient or calculated R value of 0,445 > from the R table value of 0,3610. While the coefficient of determination or the magnitude of the contribution of the influence of variable X on variable Y is 0,198 or equal to 19,8% an the equation Y =70,244 – 0,563X.